(untitled) (Промышленный Транспорт Казахстан, 2025)
Currently, the issues of environmental protection, conservation and efficient use of water resources are one of the main important problems. One of the ways to solve this problem is to improve the technological processes of purification and treatment of natural and wastewater. In addition, providing the population with good-quality drinking water is a problem of great social and sanitary importance and preventing the infection of the population with infectious diseases. To improve the quality of drinking water consumed and its rational use, it is necessary to further introduce modern technologies, equipment and materials in the construction of drinking water supply facilities, preparation and supply of drinking water. The article discusses the selection of technological schemes and the composition of treatment facilities, installations for the preparation of reagent solutions, as well as water treatment facilities, their designs and principles of operation.